2012
DOI: 10.1098/rspb.2011.2109
|View full text |Cite
|
Sign up to set email alerts
|

Contraction type influences the human ability to use the available torque capacity of skeletal muscle during explosive efforts

Abstract: The influence of contraction type on the human ability to use the torque capacity of skeletal muscle during explosive efforts has not been documented. Fourteen male participants completed explosive voluntary contractions of the knee extensors in four separate conditions: concentric (CON) and eccentric (ECC); and isometric at two knee angles (1018, ISO101 and 1558, ISO155). In each condition, torque was measured at 25 ms intervals up to 150 ms from torque onset, and then normalized to the maximum voluntary torq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 33 publications
6
66
1
Order By: Relevance
“…For the pre -training datasets an α max value of 95% seems to be more suitable as the overall activation is lower, suggesting that setting the α max at 100% may be excessive. However, setting α max = 90% is likely too low to account for fast concentric contractions where the muscle activation appears to be enhanced compared to other types of contraction (Tillin et al 2012) and surpassed the values reported here (Table 2). Given this and the robustness of the fitting methods, setting α max to 100% in most cases is likely an assumption that will not introduce any meaningful errors.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…For the pre -training datasets an α max value of 95% seems to be more suitable as the overall activation is lower, suggesting that setting the α max at 100% may be excessive. However, setting α max = 90% is likely too low to account for fast concentric contractions where the muscle activation appears to be enhanced compared to other types of contraction (Tillin et al 2012) and surpassed the values reported here (Table 2). Given this and the robustness of the fitting methods, setting α max to 100% in most cases is likely an assumption that will not introduce any meaningful errors.…”
Section: Discussioncontrasting
confidence: 61%
“…This is, probably, due to the increased variability in the %VA values of some subjects obtained from eccentric contractions, mainly during the pre-training session. A number of factors may have been the cause of the observed variability such as the expectation of noxious stimuli (Shield & Zhou, 2004) or a possible variation between trials in the joint angle where the stimulus was applied (Tillin et al 2012). However, the DIFACT function appears to behave consistently irrespective of the range of %VA values or the presence of outlier points (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some preliminary research has considered the importance of quick neuromuscular activation in injury‐related situations (Lofvenberg et al., ; Konradsen et al., ; Bloem et al., ; Zebis et al., ) and athletic tasks (Pääsuke et al., ; Tillin et al., 2013a), these have typically involved relatively small groups that may not reflect the full diversity in the general population. Athletic tasks and postural corrections also involve explosive dynamic contractions that have received very little research attention, but appear to involve different activation strategies and capabilities than isometric contractions (Tillin et al., 2012b). Moreover, further research on the implications of the wide variability in explosive force production that we have documented is required.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic RFD has typically been assessed using different joint movements such as isolated knee extension (Dewhurst et al., ; Molina & Denadai, ), hip extension (LaRoche et al., ), squat (Sleivert & Taingahue, ), elbow flexion and extension (Mirkov et al., ; Adamson et al., ; Ingebrigtsen et al., ), bench press (Pryor et al., ; Wilson et al., ), weightlifting movements (Haff et al., ; Kilduff et al., ; Comfort, ) and different jump tests either with CMJ and DJ or without SJ stretch‐shortening cycle involvement (SSC) (Haff et al., ; Marcora & Miller, ; Kawamori et al., ; McLellan et al., ; Jakobsen et al., ). Although only few studies have compared RFD values across different contraction modes (Pryor et al., ; Wilson et al., ; Haff et al., , ; Tillin et al., ), it seems that different muscle actions (concentric, eccentric, isometric or SSC) produce large variations in RFD. In general, the results of these studies indicate that absolute RFD values are lower during isometric compared to concentric (Pryor et al., ; Wilson et al., ; Haff et al., , ) or eccentric (Pryor et al., ) test contractions, whereas the differences between absolute concentric and eccentric RFD remain less clear (Pryor et al., ).…”
Section: Methodological Considerations In Rate Of Force Development Amentioning
confidence: 99%